The sex‐specific prognostic utility of sarcopenia in cirrhosis. Issue 6 (9th August 2022) - Lowe, Ryan; Hey, Penelope; Sinclair, Marie
Abstract: Sarcopenia is an increasingly recognized complication of cirrhosis that is associated with morbidity and mortality. Differences in the prevalence and prognosis of sarcopenia between men and women have been reported in other patient groups, but there is insufficient understanding of how sex impacts the prognostic value of sarcopenia in cirrhosis. A search of MEDLINE and Embase was conducted from earliest entries to April 2021. Studies were included if they examined sex‐stratified mortality impact of reduced muscle function or mass in outpatient populations with cirrhosis. We identified 700 studies of which 6 were deemed relevant for inclusion in this narrative review. Studies of interest were heterogeneous, precluding pooling of data and making interpretation of the literature challenging. Muscle mass was assessed in five studies ( n  = 2566, 1730 men, 836 women) and was reduced in 36–50% of men and 24–43% of women. All five studies found that reduced muscle mass determined by computed tomography, dual‐energy X‐ray absorptiometry, and bioelectrical impedance analysis was associated with increased mortality in men. Of these, two studies identified a corresponding relationship in women; reduced muscle mass defined by computed tomography was associated with increased mortality [hazard ratio (HR) 2.82, P  = 0.001], while increasing muscle mass by bioelectrical impedance analysis likewise conferred a survival benefit (HR 0.45, P  = 0.0016). Only one study assessed the relationship of muscle function with sex‐stratified mortality ( n  = 1405, 827 men, 578 women), concluding that reduced muscle function predicted mortality in both men and women (HR 1.65, P  < 0.001 and HR 1.54, P  < 0.001, respectively). Reduced muscle mass in cirrhosis is consistently associated with mortality in men, but lack of sex‐stratification of mortality analyses limits the ability to make strong conclusions about the impact of sarcopenia specifically in women, with even fewer data available for analysing muscle function. Improved understanding of the sex‐specific impacts of sarcopenia may help address patient deterioration and mortality while awaiting liver transplantation and allow for early intervention to mitigate mortality risk. Large, multicentre studies with adequate female participation and sex‐stratified mortality analyses are warranted.